FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP ADOPSI VARIETAS UNGGUL JAGUNG PUTIH DI KABUPATEN GROBOGAN-JAWA TENGAH - Kadar, Laila; Siregar, Hermanto; Kumala Putri, Eka Intan (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Maize is the second basic food need after rice that is potential and has high economic value in increasing income of farmers and food diversification program. White maize, in particular, is an alternative staple food in Grobogan Regency. The superior variety is a component of technology that plays a prominent role to increase productivity, disease resistant, and environmentally suitable (specific location). The aim of the study was to determine the influential factors in the adoption of superior variety of white maize in order to achieve transfer of technology. The study was carried out in three villages of Grobogan Regency, Central Java: namely Sumber Jatipohon, Godan, and Karangasem. The locations were determined with purposive sampling and the number of respondents interviewed was 120 farmers (40 farmers in each village) between September-December 2015. Analyses of the data were descriptively and quantitatively using percentages, charts and tables with logistic regression. The results of this study showed that the interest of farmers to adopt new superior variety of white maize was quite good around 66.7 percent. Farmers’ interest toward superior variety may be considered high. While factors significantly influencing the adoption included income, knowledge or information on technology, agriculture extension support, pest, and availability of seeds. On the other hand, factors which were not significantly affecting the adoption included age, formal education, farmers’ experience, and land size.